1997
DOI: 10.1093/clinids/24.3.422
|View full text |Cite
|
Sign up to set email alerts
|

Atovaquone for Salvage Treatment and Suppression of Toxoplasmic Encephalitis in Patients with AIDS

Abstract: To examine the efficacy of atovaquone as salvage therapy in patients with AIDS-related toxoplasmic encephalitis, 93 patients with AIDS and toxoplasmic encephalitis who were intolerant of standard therapy (pyrimethamine plus sulfadiazine or clindamycin) or for whom such therapy was failing were treated with atovaquone tablets (750 mg four times daily) for 18 weeks. Plasma levels of atovaquone were measured with high-pressure liquid chromatography, and the clinical and radiological responses and survival were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 13 publications
0
36
0
1
Order By: Relevance
“…This therapeutic regimen has been confirmed for its efficacy and safety in a single available randomized clinical trial (Canessa et al, 1992;Torre et al, 1998;Dedicoat & Livesley, 2006;Béraud et al, 2009). Several alternative therapies, principally used in patients who are intolerant to this combination, have been reported to be effective, including clindamycin and pyrimethamine or sulfadiazine (Katlama et al, 1996a;Tsai et al, 2002), clarithromycin and pyrimethamine (Fernandez-Martin et al, 1991), clindamycin and 5-fluoro-uracil (Dhiver et al, 1993), azithromycin and pyrimethamine (Saba et al, 1993;Jacobson et al, 2001), clindamycin and fansidar (Nissapatorn et al, 2004), sulfadoxine and pyrimethamine (Amogne et al, 2006), and atovaquone (Torres et al, 1997). There was no superior regimen among the three following combinations: pyrimethamine plus sulfadiazine, pyrimethamine plus clindamycin (Katlama et al, 1996a), and pyrimethamine plus sulfadiazine with Co-trimoxazole (Torre et al, 1998) that were reported in a recent review of comparative studies (Dedicoat & Livesley, 2006).…”
Section: Anti-toxoplasma Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…This therapeutic regimen has been confirmed for its efficacy and safety in a single available randomized clinical trial (Canessa et al, 1992;Torre et al, 1998;Dedicoat & Livesley, 2006;Béraud et al, 2009). Several alternative therapies, principally used in patients who are intolerant to this combination, have been reported to be effective, including clindamycin and pyrimethamine or sulfadiazine (Katlama et al, 1996a;Tsai et al, 2002), clarithromycin and pyrimethamine (Fernandez-Martin et al, 1991), clindamycin and 5-fluoro-uracil (Dhiver et al, 1993), azithromycin and pyrimethamine (Saba et al, 1993;Jacobson et al, 2001), clindamycin and fansidar (Nissapatorn et al, 2004), sulfadoxine and pyrimethamine (Amogne et al, 2006), and atovaquone (Torres et al, 1997). There was no superior regimen among the three following combinations: pyrimethamine plus sulfadiazine, pyrimethamine plus clindamycin (Katlama et al, 1996a), and pyrimethamine plus sulfadiazine with Co-trimoxazole (Torre et al, 1998) that were reported in a recent review of comparative studies (Dedicoat & Livesley, 2006).…”
Section: Anti-toxoplasma Therapymentioning
confidence: 99%
“…In AIDS patients, the only study to report failure with atovaquone during treatment found that a high temperature may induce inactivation of the product in the absence of food intake (Duran et al, 1995). Atovaquone has consistently been found to be a promising therapeutic for salvage therapy in CT patients who were intolerant to or who failed standard regimens (Guelar et al, 1994;Katlama et al, 1996a;Torres et al, 1997;Chirgwin et al, 2002). However, the role of atovaquone in the treatment and prophylaxis of CT in AIDS patients is not well defined and more studies are required before a firm recommendation can be made (Baggish & Hill, 2002).…”
Section: Anti-toxoplasma Therapymentioning
confidence: 99%
“…The rationale for the evaluation of Malarone for the chemoprophylaxis of malaria was based on the synergistic activity of atovaquone and proguanil hydrochloride shown in vitro 19 and in the treatment studies, 12 the good safety profile of each component established in both short and longer term use, [20][21][22] and the tolerance and safety of the combination established with the three-day therapeutic treatment regimen. [11][12][13][14] Malaria prophylaxis studies can be conducted either in subjects living in endemic areas or, alternatively, in travelers who are visiting endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…With its low cost, availability in parenteral form with excellent diffusion into the CNS and wide availability in developing countries, TMP-SMZ thus could be the first-line drug regimen for curative treatment and prophylaxis of TE, especially in resource-poor settings (Torr et al, 1998;Dedicoat & Livesley, 2008;Béraud et al, 2009). Atovaquone was studied as salvage therapy in AIDS patients with TE who were intolerant or failed PY+S or PY+C therapy (Torres et al, 1997). With a dose of 750 mg four times daily, 52% and 37% of patients were clinically and radiologically improved during the acutetherapy phase (the first 6 weeks), respectively, while 26% and 15% remained clinically or radiologically improved by week 18.…”
Section: Drugmentioning
confidence: 99%